1993
DOI: 10.1165/ajrcmb/8.5.538
|View full text |Cite
|
Sign up to set email alerts
|

Fibulin's Organization into the Extracellular Matrix of Fetal Lung Fibroblasts Is Dependent on Fibronectin Matrix Assembly

Abstract: Fibulin is a newly described extracellular matrix (ECM) glycoprotein whose function has not been elucidated. We have observed that cultured fetal lung fibroblasts produce fibulin and have postulated that its expression may be important during lung development. To begin to understand the potential function of fibulin in lung development, we examined its expression and distribution in cultured fetal lung fibroblasts. Immunofluorescence staining of cultured fibroblasts revealed that fibulin was distributed upon t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Others have shown that cells that lack fibronectin fibrils also lack tenascin C fibrils (Chung and Erickson, 1997). In addition, fibronectin deposition regulates the deposition of fibulin (Roman and McDonald, 1993;Godyna et al, 1995b;Sasaki et al, 1996) and fibrinogen (Pereira et al, 2002) in the extracellular matrix. Our data indicate that collagen I and thrombosponin-1 are deposited into fibrillar structures in the extracellular matrix only when fibronectin fibrils are present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have shown that cells that lack fibronectin fibrils also lack tenascin C fibrils (Chung and Erickson, 1997). In addition, fibronectin deposition regulates the deposition of fibulin (Roman and McDonald, 1993;Godyna et al, 1995b;Sasaki et al, 1996) and fibrinogen (Pereira et al, 2002) in the extracellular matrix. Our data indicate that collagen I and thrombosponin-1 are deposited into fibrillar structures in the extracellular matrix only when fibronectin fibrils are present.…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin contains binding sites for a number of extracellular matrix molecules, including collagens, proteoglycans, fibulin, and thrombospondin (Yamada, 1989;Hynes, 1990;Chung et al, 1995;Sasaki et al, 1996) and has been shown to be required for the matrix deposition of fibulin and fibrinogen (Roman and McDonald, 1993;Sasaki et al, 1996;Pereira et al, 2002). In addition, inhibition of fibronectin matrix deposition has been correlated with a reduction in collagen type I deposition (McDonald et al, 1982).…”
Section: Deposition and Retention Of Thrombospondin-1 And Collagen I mentioning
confidence: 99%
“…5). Fibronectin is known to be important for the deposition of several noncollagenous ECM molecules into fibrillar structures (15,63,67,76), some of which are known to bind to collagens (17,22,70). Hence, it is possible that deposition of collagen III into matrix fibrils is fibronectin dependent but occurs due to interaction with an ECM component other than fibronectin.…”
Section: Discussionmentioning
confidence: 99%
“…The assembly of a few extracellular matrix proteins have been demonstrated to be dependent on the presence of fibronectin, including collagen types I and III and thrombospondin-1 (McDonald et al, 1982;Sottile and Hocking, 2002;Velling et al, 2002;Li et al, 2003), fibulin-1 (Roman and McDonald, 1993;Godyna et al, 1995), fibrinogen (Pereira et al, 2002), and LTBP-1 (Dallas et al, 2005). Further studies established for collagen type I, thrombospondin-1, and LTBP-1 that a continuous assembly and supply of fibronectin is a prerequisite for matrix stability of these proteins Dallas et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This portion of the molecule is directly followed by the binding site for collagen/gelatin, which is located between FNI 6 and FNI 9 (Engvall et al, 1978;Balian et al, 1979;Shimizu et al, 1997). Although a plethora of reports have been published on the initial assembly mechanisms for fibronectin, virtually nothing is known about how individual fibronectin molecules are spatially oriented and organized in early and fully assembled fibronectin networks.The assembly of a few extracellular matrix proteins have been demonstrated to be dependent on the presence of fibronectin, including collagen types I and III and thrombospondin-1 (McDonald et al, 1982;Sottile and Hocking, 2002;Velling et al, 2002; Li et al, 2003), fibulin-1 (Roman andMcDonald, 1993;Godyna et al, 1995), fibrinogen (Pereira et al, 2002), and LTBP-1 (Dallas et al, 2005). Further studies established for collagen type I, thrombospondin-1, and LTBP-1 that a continuous assembly and supply of fibronectin is a prerequisite for matrix stability of these proteins Dallas et al, 2005).…”
mentioning
confidence: 99%